Trabectedin for sarcomas in daily clinical practice: analysis of 45 patients treated in a French institution. (1st November 2016) - Daupin, Johanne; Paubel, Pascal; Fillon, Julie; Debrix, Isabelle; Soares, Daniele G.; Lotz, Jean-Pierre
Abstract : Introduction : The active clinical research programme of trabectedin continues to improve knowledge on the therapeutic activity and toxicity of the drug in the treatment of soft tissue sarcomas (STS). In contrast, limited number of data is available on its use outside of clinical trials. Patients and Methods : We retrospectively analysed efficacy and safety of trabectedin when given in daily practice to patients with advanced/recurrent STS. Outcomes were compared with previously published works including clinical and retrospective studies. Results : Forty-five patients received trabectedin between January 2005 and May 2014. Sarcomas were histologically heterogeneous in our cohort (37.9% of other types of sarcomas than L-sarcomas). Our patients had poor baseline health status (ECOG ≥ 2 [17.8%]) and had received multiple previous lines of chemotherapy. Patients received a median of five cycles of treatment (1–22). The objective response rate was statistically superior in our study (37.8%) compared to the other works. However, median PFS was similar. Trabectedin-related serious adverse events (AEs) induced hospitalizations and treatment discontinuation in 22 and 15% of patients. Conclusion : This analysis confirms the efficacy of trabectedin in clinical practice (with a third of patients experiencing prolonged disease control) and highlighted the importance of its administration as early line therapy to allow the best management of serious AEs.